YAC clone contigs surrounding the Zfx and Pola loci on the mouse X chromosome. - Hamvas, R; Larin, Z; Brockdorff, N; Rastan, S; Lehrach, H; Chartier, F; Brown, S (1993)
Pulsed-field mapping of a number of DNA markers in the Pola-Zfx region of the mouse X chromosome has established a genomic restriction map extending over 1.4 Mb. A number of YAC clones from the Pola-Zfx region have been isolated from three mouse YAC libraries--first, a mouse C57BL/10 partial R1 YAC library constructed in a yeast strain carrying a rad52 mutation (Chartier et al. (1992) Nature Genetics 1: 132-136); second, a mouse C3H partial R1 library (Larin et al. (1991) Proc. Natl. Acad. Sci. USA 88: 4123-4127); and third, a mouse C57BL/6 partial R1 library (Burke et al. (1991) Mamm. Genome 1:65). Six YAC clones encompass the Zfx-Pola region, confirming the linkage of the Pola and Zfx loci and establishing a physical map order in this region of cen-Pola-DXCrc140-DXCrc57-Zfx-tel. The close linkage of Pola and Zfx in the mouse genome suggests that the POLA and ZFX loci must also be closely linked on the human X chromosome.